The Aspects of Manufacturing and Quality Control of Somatic Medications Based on Mesenchymal Stem Cells - O. A. Rachinskaya; E. V. Melnikova; V. A. Merkulov (Антибиотики и Химиотерапия, 2025)
The aim of the study was to review the international experience in ensuring the quality of medicinal products based on mesenchymal stem/stromal cells (MSCs) in order to identify the aspects of the quality control strategy during manufacturing and expert assessment within the state registration procedure in the Russian Federation.   Material and methods. The presented materials are obtained from the regulatory documents of the USA, EU, Australia, the Republic of Korea and Japan, official website of the International Society for Stem Cell Research, as well as published scientific studies.   Results. Currently, eight products containing MSCs are approved for commercial use globally, and about a thousand are in different phases of clinical trials. When the experience of quality control of these products was analyzed, aspects and risks associated with their manufacture, as well as the nature of the cellular component, were identified. Thus, the use of donor material and reagents of animal origin poses a risk of infection and the development of immunogenicity; the cultivation MSCs is associated with the risk of tumorigenicity; the formation of intermediate products during the manufacturing process and their cryopreservation leads to the creation and characterization of cell banks; the variety of mechanisms of action of MSCs requires a clear explanation of the method of achieving a therapeutic effect; the variability of donor material and cell processing methods makes it difficult to obtain a product with a reproducible composition. These aspects and risks form the basis of the strategy and standardization of quality control for this product group. As a result, quality control acquires a number of aspects: an orthogonal approach to studying the identity and potency, confirming the mechanism of action; the requirement of cell characterization during the cultivation, as well as compilation of separate specifications for intermediate products and the active substance; conducting studies of impurity content, immunogenicity (for allogeneic products) and tumorigenicity; the possibility of lack of sterility and mycoplasma test results at the time of administration to the patient.